Factors Influencing E-Procurement on the Implementation of Public Institution in Rwanda: A Case of Kigali City (2014-2016) - Gedion Alang’o Omwono; Sazir Nsubuga Mayanja; Karekezi Rodrigue (Randwick International of Social Science Journal, 2020)
The purpose of this study was to examine factors influencing e-procurement on the implementation of public institution in Rwanda a case of Kigali city (2014-2016. This study employed a descriptive research design with a sample size of 86 respondents. Questionnaires and document analysis were the main data tool. Data was presented using frequency tables, mean and standard deviation and the relationship between the variables was established using regression analysis. This study found that a well-organized e-procurement system contributes to good governance by increasing confidence, transparency, and competition and reduce the cost of doing business. The study concluded the public sector has established specific goals for the e-procurement initiatives and communicates e-procurement needs to all stakeholders. The study recommends for adaptation of the appropriate Information and Communications Technologies (ICT) necessary for successful implementation of procurement strategy more Especially procurement staff should be knowledgeable in e-procurement practices and requirements they should have the best skills and expertise on the systems.